Evaluation of Anchovy Fish Meal with or without Added Fish Solubles on Nursery Pig Performance - Ethan B. Stas; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 1,134 pigs (L337 × 1050 PIC; initially 10.4 lb) were used to evaluate anchovy fish meal with or without added fish solubles on nursery pig performance in a commercial environment. At weaning, pigs were allotted to 1 of 3 dietary treatments containing three different specialty protein sources added on an SID Lys basis. Dietary treatments consisted of a control diet containing enzymatically treated soybean meal at 7.0% of the diet, a diet containing 5.1% anchovy fish meal, and a diet containing 5.33% anchovy fish meal with added anchovy fish solubles. Pigs were fed experimental diets in phases 1 and 2 based on feed budget with phase 1 fed at 5 lb/pig and phase 2 fed at 12 lb/pig. Experimental diets were fed for approximately 21 d after weaning. Following experimental diets, all pigs were fed a common corn-soybean meal-based diet until the completion of the study. There were no differences in growth performance throughout the experimental period (d 0 to 21). During the common period (d 21 to 42), pigs previously fed anchovy fish meal with added fish solubles had improved (P<0.05) feed efficiency compared to pigs fed the control diet, with those fed anchovy fish meal alone intermediate. Overall (d 0 to 42), there was a tendency was observed (P= 0.070) where pigs fed anchovy fish meal with added fish solubles had numerically better feed efficiency compared to the other treatments. In conclusion, feeding pigs anchovy fish meal alone resulted in no differences in growth compared to pigs fed diets with enzymatically treated soybean meal, but utilizing anchovy fish meal with added anchovy fish solubles in early nursery diets improved feed efficiency late in the nursery period.
Keywords: Anchovy fish meal; fish solubles; nursery pig